(3GdSeGA hGdYGdes - (3CHh YHO Gddg eMeO Hf GHGf Hf SYjO GddNej GdbQWHj,J (B354 (3g` s
(3ChdgG (B:s
(3HGH eG jbGd ai hSW GdEfSGf jbGd GdhSW GdEfSGf (B: (3GdLgQI hGdJLQI hGdeMRe hGdHgQI hGdLhR jbGd Efg GdYXje GdLgQI hGdHgQI Ci Cfg EfSGf YXje GdhSW hjbGd CjVkG Efg dYXje GdLhR jYfi GdhSW s
(3BNQgG (B:s
(3hbGd HYV GdYdeGA (B: (3dGjSJYed gPG EdG ai TOI GdYjT , jQGO Hg Cf GdeQCI dGJfGOi hdjOgG hdGJHGdi Hg GdUYhHI MGdgG Je GdSaQ GdKGdK jJdhg HYhf Gddg JYGdi (B: (3HGH dZGJ GdKQjO hUaGJgG s
(3Ydi feW eYLe GdeNUU dGHf SjOgs
(3HChdgG JMHjS GdhRjQ CHj GdMSf GdhWGSi HJGQjN (B855(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs